Survey of Differences In Endurance Levels of Soccer Players with Various Positions - Phangga Reki Paskalis; Isti Dwi Puspita Wati; Rubiyatno Rubiyatno (JUMORA: Jurnal Moderasi Olahraga, 2022)
This study aims to determine the level of endurance of players in different positions in soccer games. The research method used in this study is a survey method with testing and measurement techniques. The population in this study is the SSB Macan Tutul players in 2021, as many as 22 players, using total sampling by making the population a sample. The results of the study are calculated based on the player's position and criteria in the SSB Macan Tutul group in 2021. The results of the study based on the position of the players showed that the goalkeeper position got an average score of 41, the defender 42.7, the midfielder 44, and the attacker 42.3, and none of them met the VO2max standard. Based on the criteria for the 2021 SSB Macan Tutul group, it shows that in the very good category (4.5%) or as many as 1 person, good (27.3%) or as many as 6 people, moderate (40.9%) or as many as 9 people, bad (27.3%) or as many as 6 people, and very bad (0%) or not at all. The player who has the highest VO2max is the midfield player, with a value of 48.8 ml/kg/min. The player with the lowest VO2max is the goalkeeper, with a value of 40.8 ml/kg/min, compared to an average player’s VO2max of 43 ml/kg/min. Keywords: Endurance Level, Player Position, VO2max